A new definition for metabolic dysfunction-associated fatty liver disease: An international expert consensus statement - YILMAZ, YUSUF (ELSEVIER, 2020)
The exclusion of other chronic liver diseases including excess alcohol intake has until now been necessary to establish a diagnosis of metabolic dysfunction-associated fatty liver disease (MAFLD). However, given our current understanding of the pathogenesis of MAFLD and its rising prevalence, positive criteria to diagnose the disease are required. In this work, a panel of international experts from 22 countries propose a new definition for the diagnosis of MAFLD that is both comprehensive and simple, and is independent of other liver diseases. The criteria are based on evidence of hepatic steatosis, in addition to one of the following three criteria, namely overweight/obesity, presence of type 2 diabetes mellitus, or evidence of metabolic dysregulation. We propose that disease assessment and stratification of severity should extend beyond a simple dichotomous classification to steatohepatitis vs. non-steatohepatitis. The group also suggests a set of criteria to define MAFLD-associated cirrhosis and proposes a conceptual framework to consider other causes of fatty liver disease. Finally, we bring clarity to the distinction between diagnostic criteria and inclusion criteria for research studies and clinical trials. Reaching consensus on the criteria for MAFLD will help unify the terminology (e.g. for ICD-coding), enhance the legitimacy of clinical practice and clinical trials, improve clinical care and move the clinical and scientific field of liver research forward. (C) 2020 European Association for the Study of the Liver. Published by Elsevier B.V. All rights reserved.
Keywords: MAFLD; Cirrhosis; Diagnostic criteria; Metabolic; NAFLD; Steatohepatitis; Diabetes; Obesity; HIGH BLOOD-PRESSURE; NONALCOHOLIC STEATOHEPATITIS; HISTOLOGIC FEATURES; NATURAL-HISTORY; HEALTHY OBESE; MANAGEMENT; DIAGNOSIS; NAFLD; PROGRESSION; PREVALENCE